PROBLEMA PENGGANTIAN HUKUM-HUKUM KOLONIAL DENGAN HUKUM-HUKUM NASIONAL SEBAGAI POLITIK HUKUM - Maroni, Maroni (Jurnal Dinamika Hukum, 2012)
Replacement of colonial law was committed by Indonesia since the first, but fact there are still lot of colonial law have a status as positive law. The problems, what is the problematic causing factors of replacement colonial law with national law and how the politics of law response its problematics? The results of the study describe that the causing factors consist of (a) the heterogeneity of Indonesian nation, (b) embrace the principle of unification and codification; (c) differences in views on human rights. While, the politics of law formed as guidance for the colonial laws which are difficult to change such the law that relating to social life, cultural and spiritual. In other case, the field of "neutral" law such contract law and in the field of commercial law changing by renewal or creation the law. Keywords: Problems, colonial, national, politics of law